The complete chloroplast genome of Chusquea culeou (Poaceae: Bambusoideae: Bambuseae) - Xianzhi Zhang; Siyun Chen; Ping Chen; Hong Liang (Mitochondrial DNA. Part B. Resources, 2019)
Chusquea culeou is one important ornamental bamboo in gardens to form a substantial clump of greenery. At present, the genetic data of this species are scarce. In this study, we produced the complete chloroplast (cp) genome of C. culeou by genome skimming. The complete cp genome is 138,137 base-pairs (bp) in size, with a large single copy region (LSC) of 81,671 bp and a small single copy region (SSC) of 12,858 bp which are separated by a pair of inverted repeats (IRs) of 21,804 bp. The genome contained a total of 132 genes, including 84 protein-coding genes, 40 transfer RNAs and 8 ribosomal RNAs. There were 12 intron-containing genes. The GC content of the cp genome is 38.8% and protein-coding regions make up 43.5% of this cp genome. Phylogenomic analysis strongly supported C. culeou locating in the neotropical woody bamboos lineage, being closely related to C. liebmannii and C. circinata.